Factors Affecting Nutritional Status among Children Aged 12–23 Months - Tisnasari Hafsah; Lina Shabrina Qorib Sudaryo; Yovi Yoanita (Althea Medical Journal, 2019)
Background: In Indonesia about 18% of children, mostly in the first two years of life, are malnourished, causing a serious impact. Many factors are thought to affect nutritional status among young children. This study was conducted to determine factors affecting the nutritional status of children aged 12–23 months in West Java, Indonesia.